O tempo e o espaço da administração educacional na formação do pedagogo: um mapeamento a partir dos projetos político-pedagógicos de universidades públicas - Barbosa, Andréa Haddad [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study had as main objective to map the space of educational administration in the initial training of the pedagogue in public universities in different Brazilian states , from a historical perspective of educational administration and pedagogy courses . The approval of the School of Education National Curriculum Guidelines in 2006 , fostered numerous questions , among them , the aspects related to the formation of the pedagogue as administrator / manager . In the opinion of some authors , such a document to emphasize that it is the teacher participate in the management favors to various interpretations , which may have negative consequences in the formation of this professional . Considering this perspective , this research question has been crafted as this area of knowledge in initial teacher training in different states. As procedures , this documentary study works with a qualitative approach to conduct one hand , the literature survey and systematization and, secondly , the survey, systematization and analysis of some elements in the political- pedagogical projects , accessed from the internet pages of Pedagogy courses . Data were collected during 2011 and 2013 and organized considering the following items : listing of graduates , curriculum and menus . The sample set was composed of 30 state universities and 34 public universities . The collected data were subjected to content analysis procedures . As public universities results revealed a rather significant surge workload for the study and practice in educational administration . The analysis of the menus revealed a great diversity regarding content prioritized training. These data suggest different understandings of educational administration and the importance of this professional training in pedagogy course . The differences , so expressive , among the realities reflect the inaccuracies of the National Curriculum Guidelines as...

O presente estudo teve como objetivo geral mapear o espaço da administração educacional na formação inicial do pedagogo em universidades públicas nos diferentes estados brasileiros, a partir de uma perspectiva histórica da administração educacional e do curso de Pedagogia. A aprovação das Diretrizes Curriculares Nacionais do Curso de Pedagogia, em 2006, fomentou inúmeros questionamentos, entre eles, os aspectos relacionados à formação do pedagogo enquanto administrador/gestor. No entendimento de alguns autores, tal documento ao enfatizar que cabe ao docente “participar” da gestão favorece a várias interpretações, o que pode ter consequências negativas na formação desse profissional. Considerando tal perspectiva, esta pesquisa questiona como vem sendo trabalhada essa área de conhecimento na formação inicial do pedagogo em diferentes estados brasileiros. Como procedimentos, este estudo documental trabalha com a abordagem qualitativa ao realizar, por um lado, o levantamento e sistematização bibliográfica e, por outro, o levantamento, sistematização e análise de alguns elementos contidos nos projetos políticopedagógicos, acessados pela internet nas páginas dos cursos de Pedagogia. As informações foram coletadas durante o período de 2011 e 2013 e organizadas considerando os seguintes itens: perfil do egresso, matriz curricular e ementas. O conjunto amostral foi composto por 30 universidades estaduais e 34 universidades federais. Os dados coletados foram submetidos aos procedimentos de Análise de Conteúdo. A análise do material coletado revelou uma oscilação bastante significativa de carga horária para o estudo e prática em administração educacional. O estudo das ementas indicou uma diversidade muito grande quanto aos conteúdos priorizados na formação. Tais dados sugeriram diferentes entendimentos da administração educacional e da importância da formação desse profissional no curso de...
Keywords: Escolas - Organização e administração; Professores - Formação; Administradores escolares - Formação; Universidades e faculdades - Planejamento; Educação - Currículos; Teachers, Training of